ONE NEW SPECIES OF THE GENUS HIRSCHMANNIELLA LUC AND GOODEY, 1963 AND NEW HOST RECORD FROM MANIPUR, INDIA - I. GYANESWORI,; R. K.GAMBHIR, (The Bioscan, 2013)
During a survey of nematodes associated with citrus plants in Manipur, revealed the presence of one new species of the genus Hirschmanniella Luc and Goodey, 1963. The new species was recovered from the soil around the Citrus maxima (Lemon) plant, which is a new host record. Hirschmanniella is distinguished by having longer stylet, oesophagus and longer tail length with a single mucro in both male and female species.